Thrombin-Derived Host-Defense Peptides Modulate Monocyte/Macrophage Inflammatory Responses to Gram-Negative Bacteria - Hansen, Finja C.; Strömdahl, Ann-Charlotte; Mörgelin, Matthias; Schmidtchen, Artur; van der Plas, Mariena J. A. (Frontiers in Immunology, 2017)
Host defense peptides play a fundamental role in the innate immune system by modulating inflammatory responses. Previously it was shown that the thrombin derived host defense peptide GKY25 inhibits LPS-induced responses of monocytes and macrophages in vitro, ex vivo and in vivo. In this study, the effect of GKY25 on the interaction of monocytes/macrophages with Gram-negative bacteria was explored. Electron microscopy analysis showed that fibrin slough from non-healing wounds, colonized with S. aureus and P. aeruginosa, contains C-terminal thrombin epitopes associated with these bacteria extracellularly and in phagosomes of leukocytes. Live imaging of RAW 264.7 cell cultures showed binding of GKY25 to E. coli BioParticles extracellularly, and colocalization intracellularly. Although peptide binding did not alter the rate of phagocytosis, GKY25 reduced NF-kB/AP-1 activation and subsequent cytokine release in response to both heat-killed and live bacteria. Notably, preincubation of RAW 264.7 cells with peptide did increase BioParticle uptake in a dose-dependent manner. Taken together, the thrombin-derived host defense peptide GKY25 binds to bacteria extracellularly, and colocalizes with bacteria intracellularly, thereby reducing pro-inflammatory responses.